Enhancing Learning Awareness of English Teachers in Indonesia’s Elementary Schools: A Lesson Study - Klara Tyas Sulistyawati; Kuswandono, Paulus (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
Enhancing teachers’ learning awareness can be done by conducting lesson studies. Lesson study itself is a collaborative project where the teachers can share their knowledge and skills to improve teaching performances continuously. Although lesson study is useful, it may have a different result if it is implemented in online mode, particularly during the pandemic situation, because the teachers cannot always meet physically with their colleagues and the students. Thus, the researchers are interested to analyze the lesson study implemented during this pandemic situation. This research aims to find out how lesson study can improve teachers’ learning awareness during this pandemic situation. In this research, the participants are five English teachers from different elementary schools in Indonesia. To gain the data, the researchers implemented a case study method. Besides, the researchers used interview guidelines and an observation sheet. After collecting and analyzing the data, the researchers concluded that the teachers could enhance their learning awareness by implementing the following procedure: knowing their role in the learning process and knowing attractive learning activities.